2018
DOI: 10.1158/2326-6066.cir-18-0129
|View full text |Cite
|
Sign up to set email alerts
|

The Mutation-Associated Neoantigen Functional Expansion of Specific T Cells (MANAFEST) Assay: A Sensitive Platform for Monitoring Antitumor Immunity

Abstract: Mutation-associated neoantigens (MANA) are a target of antitumor T-cell immunity. Sensitive, simple, and standardized assays are needed to assess the repertoire of functional MANA-specific T cells in oncology. Assays analyzing in vitro cytokine production such as ELISpot and intracellular cytokine staining have been useful but have limited sensitivity in assessing tumor-specific T-cell responses and do not analyze antigen-specific T-cell repertoires. The FEST (Functional Expansion of Specific T cells) assay de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 48 publications
(54 reference statements)
1
123
0
Order By: Relevance
“…Lastly, some promising tests have been developed in the field of immuno-oncology using T cells for the analysis [135][136][137][138][139]. T cells can easily be isolated from the patients' blood by density centrifugation and selection of CD4 þ or CD8 þ cells by flow cytometry (using fluorescence or magnetic beads) [135].…”
Section: T-cell Receptor Repertoirementioning
confidence: 99%
“…Lastly, some promising tests have been developed in the field of immuno-oncology using T cells for the analysis [135][136][137][138][139]. T cells can easily be isolated from the patients' blood by density centrifugation and selection of CD4 þ or CD8 þ cells by flow cytometry (using fluorescence or magnetic beads) [135].…”
Section: T-cell Receptor Repertoirementioning
confidence: 99%
“…The prediction of the TCR antigen specificity based on the TCR amino-acid sequence alone is extremely challenging. This issue has been recently addressed by generating a large database of antigen-specific TCR sequences and elaborating algorithms that accurately identify the patterns of sequence motifs that correlated with antigen specificity [89]. By this approach, it has been possible to identify neoantigen-specific T-cell clones in the neoadjuvant setting and to track neoantigen-specific T-cell clones in blood upon anti-PD-1 therapy [75].…”
Section: Analysis Of Immune Repertoirementioning
confidence: 99%
“…Then, the authors addressed the hypothesis that a substantial component of antitumor immunity after PD-1 blockade is directed toward mutation-associated neoantigens. To this end, they used a web-based bioinformatics platform that identify mutation-associated neoantigen-specific T-cell clones [89], and demonstrated that in a patient showing a complete pathological response, T-cell clones specific for mutation-associated neoantigens were rapidly expanded in peripheral blood after neoadjuvant PD-1 blockade [73].…”
Section: Lung Cancermentioning
confidence: 99%
“…A technology named MANAFEST (Mutation-Associated Neoantigen Functional Expansion of Specific T Cells), incorporates multiple techniques including WES, T cell receptor sequencing and comprehensive bioinformatics, proposes actionable tumor mutations and even includes peptidestimulated cultures, to ultimately achieve an all-encompassing, anti-tumor immunity surveillance. This approach is uniquely poised to gauge a patient's own immune response to their tumor, but whether its clinical utility will be superior in patients with high or low neoantigen burden, remains to be determined (Danilova et al, 2018). Different mutation loads in tumors are also present in virus-associated cancers, characterized by a specific immunological profile (Sivanandam et al, 2019).…”
Section: Tumor Neoantigens: the More The Merriermentioning
confidence: 99%